Uneven Distribution Of Material Living Conditions (WEALTH): Lithuanian Case - Ona Gražina Rakauskienė; Lina Volodzkienė (Torun Business Review, 2017)
Economic inequality has become one of the most relevant problems of the global economy. Economic inequality reduces social and economic welfare. The problem of economic inequality is specific and complex by nature. Conventionally, economic inequality is measured using such methods as differentiation of income and consumption of the population, however, in order to find out the real level of inequality, the differentiation of wealth should be studied as well. For this reason, the main aspects to be analysed in this article are to identify and emphasize the inequality of material living conditions as an inseparable part of economic inequality in Lithuania and, as a result, poor quality of life and obstacles in the way of economic progress. This research is funded by the Research Council of Lithuania (No. GER-009/2015).